The COVID-19 Pandemic is a Clarion Call for a Systems-Thinking Based Approach - Buthelezi, Phakamani M (Journal of Sustainable Development Law and Policy, 2025)
This qualitative research-based study evaluates the level of preparedness of newly qualified higher learning entrants to higher learning centers. The outbreak of the Covid-19 pandemic has brought about an unexpected innovation to higher education. The post effects are a clarion call to the global community to jointly collaborate, integrate and interconnect learning to cope with any unexpected pandemic in the future. The pandemic is continuously making an abecedarius of a systems-thinking based approach. Whilst learning is increasingly relying on digital technology, the overall education approach is missing an approach that integrates pre and post higher learning elements to a sustainable education system which is ready for any future pandemic. The study is based on responses of ten university students who entered the university for the first time during the COVID-19 pandemic. The students were randomly selected to answer 5 open-ended questions using a qualitative research method. The results have shown that moving from a normal school learning environment to a higher education environment was traumatic and created unnecessary confusion. Also, the support given at the time was inadequate as students had to climatize themselves with university life. The results further point out that there must be an integration between high school and university education. The integration requires adequate support for everyone involved in the education system. Importantly, the study recommends that investing in digital technology is an indispensable necessity that does not only make students to be globally competitive but makes them to be ahead of any eventuality. This study provides feedback from universities’ students/participants to better improve e-learning.